Innovational aspects of the hotel industry development - Dotsenko, Viktor; Shydlovska, Olena; Ishchenko, Tatiana; Medvid, Irina (My University, 2020)
А prerequisite for achieving economic success and ensuring the competitiveness of the hospitality industry is to develop an appropriate innovation strategy. It should be based on the novelty of services, the improvement of their technological availability, their economic and social efficiency. Considering the international experience of successful activity of the hotel industry, the alternative way of their survival in the conditions of global competition is based on an innovative basis with active use of modern scientific and technological achievements, as well as the readiness of hotels for innovation and innovations. Передумовою досягнення економічного успіху та забезпечення конкурентоспроможності підприємств індустрії гостинності є активізація інноваційної діяльності та розроблення відповідної інноваційної стратегії. Вона повинна ґрунтуватися на новизні послуг, поліпшенні технологічності їх надання, економічній та соціальній ефективності. З огляду на міжнародний досвід успішної діяльності підприємств готельного господарства, безальтернативний шлях їх виживання в умовах глобальної конкуренції побудований на інноваційній основі при активному використанні сучасних науково-технічних досягнень, а також готовності готелів до інновацій та нововведень.
Keywords: інновації (готельно-ресторанний комплекс); innovations (hotel and restaurant complex); індустрія гостинності; hospitality industry; кафедра готельно-ресторанної справи